Treatment Modality (Private or Government/Safety Net) Choices for CABG and Factors Involved in Decision Making - Saad Afzal, Yousaf Ikram, Muhammad Masood Ahmad, Muhammad Zain Ul Abidin, Muhammad Tariq, Muhammad Usman, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The treatment of cardiovascular disease is an expensive treatment and need expertise also. There are facilities in private setup as well as in government t hospital. At times it becomes difficult to choose between private and government facilities for various reason, cost and safety being the two most important factors. Objective: To assess the choice of patient for treatment of CVD as a private patient or through government/safety nets and see its association with factors involved in decision making. Study Design: Cross-sectional analytical Place and Duration of Study: Faisalabad Institute of Cardiology from 1st January 2020 to 30th June 2020. Methodology: Sixty patients chose private treatment and government/safety net treatment was assessed. Then the frequency of various factors involved was determined and their association was evaluated with choice of treatment. Results: Fifty one (85%) opted government/ safety net treatment and 9 (15%) opted private treatment. Education, Income and cost of treatment were the three major factors associated with choice of treatment having respective p-values 0.015, <0.001 and <0.001. The attitude toward consultation was also found associated with option of treatment. The median waiting time for government/safety net treatment was 129(119–143) days while for private treatment it was 3 (2–4) days. Conclusion: The frequency for choice of private treatment is very low and, those with less education and low on resources opt for government treatment while those who had better income and education and prefer to be treated earlier opt for private treatment but still take the option of government health facilities due to safety and cost concern. Keywords: CABG, Safety nets